Performance of corn grain with and without fertilization in the state of Campeche - Medina Méndez, Angel Juan; Alejo Santiago, Gelacio; Soto Rocha, Jesús M.; Hernández Pérez, Mirna (Revista Mexicana de Ciencias Agrícolas, 2018)
Maize is of great importance for the state of Campeche based on the number of producers and the cultivated area, because it is a priority crop for research and technology transfer. In the present investigation, the main objective was to determine the effect of fertilization on grain yield. The 11 hybrids were used, which were subjected to two environments, with and without fertilization. The experiment was supplied only with rainwater. The statistical analysis showed highly significant differences between fertilization treatments and hybrids. Treatment without fertilization recorded the lowest average performance. The average response to fertilization was 1 231 kg ha-1 and was in a range of 749 to 2 558 kg ha-1. On the other hand, although all hybrids responded positively to fertilization, this response was differential, influenced by the genotype-environment interaction. Fertilization was valued at 2 900 ha-1, equivalent to 878 kg of grain at current prices of 2017. With fertilization the best materials were 7W69C, MH-9058 with average yield of 6 172, 6 004 kg ha-1, which it represents net income of 9 743 and 9 188 pesos per hectare, respectively, which translates into a productivity of 0.97 and 0.92 pesos per square meter. Likewise, in unfertilized corn, the best materials were DKB-399 and 7W79C, with average yields of 5 185 and 4 748 kg ha-1, which gives rise to net income of 9 386 and 7 943 pesos per hectare, respectively and it translates into a productivity of 0.94 and 0.79 pesos per square meter. The formula of fertilization 110-46-00 applied to corn, caused an increase in net income that on average was 1 162 ha-1, which could amount to 3 815 ha-1 on average, if the most outstanding hybrids are used.